2014
DOI: 10.24252/bio.v2i1.467
|View full text |Cite
|
Sign up to set email alerts
|

Preparasi Kromosom Fase Mitosis Markisa Ungu (Passiflora edulis) Varietas Edulis Sulawesi Selatan

Abstract: Passion fruit (Passifloraceae) was derived from tropical South America. Kind of passion fruit that widely cultivated in South Sulawesi is purple passion fruit (Passiflora edulis). This study aimed to observe the activity of Passiflora edulis chromosome at different stages of cell division and observed active mitosis time. The study was conducted by using exploratory descriptive study and obtained results a mitotic on Passiflora edulis occurs at 09.00 until 15.00 pm. Prophase seen in 5 minute after observation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…This shows that the time for cell division of pigeon pea roots began at 08.00, indicated by the appearance of prophase. Previous research on prometaphase in several other plants has reported that the highest prometaphase in the roots of Passiflora edulis was found at 10.20 after prophase (Muhlisyah et al, 2014). Rindyastuti and Daryono (2009) found that the highest prometaphase in Coccinia grandis species was at 09.50-10.15 after prophase, while the prometaphase in lime and kaffir lime was found Kristin Sangur et al / Biosaintifika 13 (2) (2021): 128-134 132 mostly at 08.00 WIB (Western Indonesian Time) after prophase (Arisuryanti et al, 2007).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This shows that the time for cell division of pigeon pea roots began at 08.00, indicated by the appearance of prophase. Previous research on prometaphase in several other plants has reported that the highest prometaphase in the roots of Passiflora edulis was found at 10.20 after prophase (Muhlisyah et al, 2014). Rindyastuti and Daryono (2009) found that the highest prometaphase in Coccinia grandis species was at 09.50-10.15 after prophase, while the prometaphase in lime and kaffir lime was found Kristin Sangur et al / Biosaintifika 13 (2) (2021): 128-134 132 mostly at 08.00 WIB (Western Indonesian Time) after prophase (Arisuryanti et al, 2007).…”
Section: Resultsmentioning
confidence: 85%
“…Mitosis is the process of genome division that has been duplicated by a cell into two identical cells produced by cell division. Mitosis consists of five phases, namely prophase, prometaphase, metaphase, anaphase, and telophase (Muhlisyah et al, 2014;Sharma & Vig, 2012). It is essential that mitosis research be conducted in order to obtain the best cell phase, which is when the chromosomes are clearly visible and scattered, so that they can be easily counted.…”
Section: Introductionmentioning
confidence: 99%
“…Waktu pembelahan mitosis pada ujung akar bervariasi antara spesies yang satu dengan yang lain. Pembelahan mitosis pada pisang tongkat langit (Musa troglodytarum L.) pukul 09.00 Wit (Tuapattiyana, 2018), tanaman gaharu (Gyrinops versteegii) pukul 06.30-07.00 Wita (Iswantari et al, 2017), markisa ungu (Passiflora edulis) pukul 09.00-15.00 Wita (Muhlisyah et al, 2014), famili Solanaceae pukul 07.00-10.00 Wib (Aristya et al, 2019). Waktu pembelahan optimum pada Allium cepa dan Allium fistulosum pukul 06.00 Wib, sedangkan Allium sativum pukul 09.00 Wib (Abidin et al, 2014).…”
Section: Identifikasi Waktu Pembelahan Mitosis M Paradisiaca Cv Hajiunclassified
“…Proses preparasi kromosom merupakan kegiatan pembuatan preparat kromosom tumbuhan yang sedang aktif membelah. Kromosom dapat terlihat jelas pada fase-fase tertentu seperti metafase dan prometafase pada saat pembelahan inti (Muhlisyah et al, 2014). Prinsip preparasi kromosom adalah memperoleh sel pada berbagai fase dengan cara menghentikan aktivitas pembelahan sel dengan metode tertentu (Pack & Stratakis, 2002).…”
Section: Preparasi Kromosom Tumbuhanunclassified
“…Gambar 2. a) Prometafase pada akar markisa ungu (Passiflora edulis) 10x100; b) prometafase pada Indigofera tinctoria ((Muhlisyah et al, 2014) Pada beberapa tumbuhan dengan ukuran dan kromosom yang kecil, metode squash yang menggunakan aceto-orcein membutuhkan bantuan mikroskop resolusi tinggi. Kromosom yang tidak melekat erat pada gelas benda dan tidak tersebar akibat pemencetan yang tidak tepat mengakibatkan sel relatif masih berada pada bentuk aslinya, sehingga gambar menjadi tidak efektif (Etikawati & Setyawan, 2000).…”
Section: Tahap Maserasi Proses Maserasi Dilakukan Dengan Menggunakanunclassified